FACTORS AFFECTING THE FINANCIAL AND NON-FINANCIAL RATIOS ON GOING-CONCERN AUDIT OPINION - Icuk Rangga Bawono; Aan Kanivia; Oman Rusmana (Universitas PGRI Madiun, 2021)
ABSTRACTThis study aims to determine the factors affecting the financial and non-financial ratios' ongoing concern audit opinion. Data were obtained from 31 property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2014-2017, comprising 124 samples. The data collected were analyzed using the logistic regression analysis method. This result showed that the activity ratios, liquidity, audit quality, previous year's audit opinion, and shopping could affect the provision of a company's going concern audit opinion. Meanwhile, the ratio of profitability, solvency, and company size has a more negligible effect on the going-concern audit opinion.ABSTRAKPenelitian ini dilaksanakan dengan tujuan untuk mengetahui pengaruh rasio keuangan dan nonkeuangan terhadap opini audit going concern. Penelitian ini mengambil sampel 31 perusahaan subsektor property dan real estate yang terdaftar di Bursa Efek Indonesia (BEI) pada periode tahun 2014-2017 dengan total 124 sampel. Pengujian hipotesis menggunakan metode analisis regresi logistik. Penelitian ini menunjukkan bukti rasio aktivitas, likuiditas, kualitas audit, opini audit tahun sebelumnya, dan opinion shopping dapat memengaruhi pemberian opini audit going concern perusahaan. Sementara rasio profitabilitas, solvabilitas, dan ukuran perusahaan kurang memberikan efek terhadap pemberian opini audit going concern perusahaan.